IMPLEMENTASI REVALUASI ASET TETAP BERDASARKAN PERATURAN MENTERI KEUANGAN NO. 79 TAHUN 2008 PADA PERUSAHAAN DI INDONESIA - Dewi, Putri Nabela (Jurnal Akuntansi AKUNESA, 2014)
Regulation of Minister for Finance No. 79, 2008 regulate firms fixed asset revaluation treatment for the purpose of taxation. This paper explain the implementation of fixed asset revaluation based on Regulation of Minister for Finance No. 79, 2008 in Indonesia companies. Based on literature study simulated in case study found that if firms experience losses, firms will better revaluate fixed asset hence will generate tax saving. Fixed asset revaluation perform to present fairer revenue and cost calculated so that true ability and firms value.Keywords: Fixed asset, Asset revaluation, PMK No.79 Th 2008